Supervision of Judges in the Perspective of Pancasila Philosophy and its Implementation in the Indonesian Judiciary - Sailellah, Sirajuddin (Universitas Syiah Kuala, 2023)
This study aims to explore the supervision of judges from the perspective of the Pancasila philosophy and identify its implementation in Indonesian judicial institutions. The Pancasila philosophy is seen as a moral and ethical foundation that guides the behavior of judges in carrying out their duties. This research is library research with the meaning of judge supervision as the material object and Pancasila philosophy as the formal object. Research findings show that in the context of Pancasila, supervision of judges is not only legal, but also moral and ethical. The success of judges' supervision is reflected in the ability of judicial institutions to respect Pancasila values, such as justice, legal certainty, and balance between rights and obligations. The implementation of supervision of judges in Indonesia is realized through various mechanisms, such as the Honorary Council of Judges, the Honorary Court of Supreme Judges, and the Honorary Court of the Regional Representative Council. This study contributes to illustrating the relationship between the Pancasila philosophy and the practice of supervising judges in Indonesia, as well as offering an in-depth understanding of the challenges and potential improvements in implementing judicial supervision. The implications of this research can provide a basis for policy reform and improvement of the judge supervision system to strengthen the integrity and effectiveness of judicial institutions in Indonesia.